Neuro protective effect of Epigallocatechin Gallate (EGCG) and Vitamin- E against rotenone induced cellular model of Parkinson’s disease - SASIKUMAR.C; SWAMINATHAN.S; ARVIND BHARANI.R.S; MOHANA.S.J (International Journal of Pharma and Bio Sciences, 2018)
Parkinson’s Disease (PD) is a progressive neurodegenerative disorder, characterized by the loss of dopaminergic neurons in substantial nigra pars compact, and can be experimentally induced by the neurotoxin 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP). Chronic administration of MPTP/probenecid (MPTP/p) leads to oxidative stress, induction of apoptosis, and loss of dopaminergic neurons which results in motor impairments. Epidemiological studies have shown an inverse relationship between tea consumption and susceptibility to PD. Green tea polyphenol epigallocatechin-3-gallate (EGCG) is reported to have antioxidant abilities and to counteract beneficially mitochondrial impairment and oxidative stress. The present study was designed to investigate neuroprotective effects of EGCG on rotenone-treated dissociated cell cultures. Rotenone is a potent inhibitor of complex I of the respiratory chain, which in vitro causes pathological and neurochemical characteristics of diseases in which mitochondrial impairment is involved, e.g., Parkinson’s disease. Treatment with EGCG (0.1, 1, 10 μM) alone had no significant effects on cellular model SH-SY5Y neuroblastoma cells were obtained. On other hand neuroprotective effects of vitamin-E in separate as well as combined form of vitamin-E and EGCG on rotenone-treated dissociated cell cultures were also investigated and significant effects on cellular model SH-SY5Y were observed.